Percutaneous transforaminal endoscopic decompression for the treatment of intraspinal tophaceous gout: A case report. Issue 21 (22nd May 2020) - Chen, Xinji; Xu, Guokang; Hu, Qingfeng; Zhao, Tingxiao; Bi, Qing; Huang, Yazeng; Shao, Haiyu; Zhang, Jun
Abstract: Rationale: Intraspinal tophaceous gout is relatively rare condition presenting with major clinical manifestations, such as spinal cord or nerve roots compressions (radiculopathy). It is usually difficult to differentiate intraspinal tophaceous gout, lumbar disc herniation, stenosis of spinal canal, ossification of ligamentum flavum, and other degenerative spinal disorders from each other. Patient concerns: A 64-year-old man was admitted with a history of progressive low back pain for 11 months. He also presented with radiculopathy and numbness of his left lower extremity. Diagnoses: Preoperative computed tomography (CT) and magnetic resonance imaging (MRI) showed L4/5 disc herniation and lateral recess stenosis on the left side. During the operation of percutaneous transforaminal endoscopic decompression, intraspinal chalky white material was seen. Post-operative pathologic results confirmed the diagnosis of gouty tophi. Interventions: Percutaneous transforaminal endoscopic decompression was performed as treatment. Intraspinal chalky white material was seen. We removed most of the chalky white material and extruded nucleus. Outcomes: His symptom subsided rapidly and no deterioration was noted 1 year post-operatively. Lessons: Although intraspinal tophaceous gout is not commonly seen, clinicians should take it into consideration as a possible differential diagnosis when the patient exhibits axial pain or neurological deficits with risk factors of gout. We identified and treated this case with percutaneous transforaminal endoscopic decompression for the first time and got an excellent outcome. Percutaneous transforaminal endoscopic surgery proved to be an effective and minimally invasive alternative for identifying and treating intraspinal tophaceous gout.